Analysis and dynamic modeling of a moraine failure and glacier lake outburst flood at Ventisquero Negro, Patagonian Andes (Argentina) - Worni, Raphael (2012)
Although moraine dams are inherently prone to failure because of their often weak structure, loose internal composition and lack of an engineered spillway, the understanding of dam breaching processes remains largely incomplete and appropriate modeling approaches are scarce. This paper analyzes a recent glacier lake outburst, caused by the failure of the terminal moraine of Ventisquero Negro (Patagonian Andes, Argentina) in May 2009. The dam breach trigger, breaching and lake emptying processes, plus the dynamics of the outburst flood were reconstructed based on field evidence and the application of adynamic dam break model. Results indicate that the moraine failure was caused most probably by a rising lake level due to heavy precipitation, resulting in high lake outflow which led to dam erosion and finally to dam failure. The lake volume of ca. 10 X 10 exp 6 m3 was released in ca. 3 h, producing high-discharge (ca. 4100 m3 s1) debris flows and hyperconcentrated flows as the escaping water entrained large volumes of clastic material. The methodology presented in this paper provides valuable insights into complex dam breach and GLOF processes, and closes a critical gap in dynamic dam break modeling aimed at providing the lake outburst hydrograph. An accurate determination of outburst hydrographs constitutes one of the most crucial aspects for hazard assessment of unstable lakes and will gain further importance with ongoing glacier retreat and glacier lake formation.